THE EFFECT OF CAREER DEVELOPMENT, COMPENSATION, AND JOB COMPLEXITY ON EMPLOYEE PERFORMANCE AT SUKORAMBI COMMUNITY HEALTH CENTER, JEMBER - Maulaya, Tarista Dina; Winahyu , Pawestri; Umami, Septy Holisa (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to examine the impact of career development, compensation, and task complexity on employee performance at the Sukorambi Jember Health Center. Method: The research adopts a causal approach, utilizing a quantitative method through surveys conducted with 32 employees, representing the total sample. The independent variables in this study are career development, compensation, and task complexity, while employee performance serves as the dependent variable. Data analysis was performed using multiple linear regression techniques to understand the relationships between these variables. Results: The findings indicate that all three independent variables-career development, compensation, and task complexity-have a significant influence on employee performance. Specifically, career development was found to positively contribute to performance outcomes by enhancing employees' skills and competencies. In addition, fair and adequate compensation was shown to serve as a strong motivator, driving higher levels of work engagement and effort. Similarly, effectively managing task complexity, through proper workload distribution and support, led to improved employee performance. The coefficient of determination (R²) of 65.4% reveals that these independent variables account for a substantial portion of the variation in employee performance, suggesting their importance in shaping overall job outcomes. Novelty: This study offers valuable insights for organizations looking to enhance employee productivity, emphasizing the importance of strategic human resource management practices in fostering a more motivated and efficient workforce. By focusing on career growth opportunities, fair compensation, and task management, organizations can optimize employee performance and contribute to long-term organizational success.